Vloga bronhoskopije v diagnostiki in zdravljenju bolnišničnih pljučnic - Kovačič, Dragan (Zdravniški vestnik, 2001)
Background. The aim of our study was to evaluate the role of bronchoscopy in the diagnosis and treatment of hospital pneumonias by microbiological culturesobtained from bronchial aspirates. Methods. We included all patients treated for hospital pneumonias during 1999 in General Hospital Celje (Division of cardiology and pulmonary medical care, internal and surgical intensive care unit) in whom bronchoscopy was performed. Only the patients with obtained microbiological cultures (isolation and bacterial sensitivity toantibiotics) were studied. Results. We performed 112 bronchoscopies. Sixty-nine (62%) patients were males and 43 (38%) of female. Microbiological cultures were positive in 95 (85%) and negative in 17 (15%) specimens. Mortality rate was 32% and average length of stay was 14 days. The most frequently isolated bacteria was Pseudomonas aeruginosa (20 patients - 26%), followed by methicillin sensitive Staphylococcus aureus-MSSA in 14 patients. E. coli was present in 14 cultures and Streptococcus pneumoniae in 12 patients. Methicillin resistant Staphylococcus aureus-MRSA was found in 10 patients. Blood and central venous catheter clutures were positive in 10 patients. The same bacteria were also isolated in other specimens in 26 patients. Conclusions. Bronchoscopy is an important aid in diagnosing hospitalpneumonias. In high percentage it provides microbiological evaluation of bronchial aspirate, and has major impact in selection of an appropriate antibiotic treatment.
Keywords: antibiotic; Antibiotics; Antibiotiki; bolezni dihal; Bolnišnične okužbe; Bronchoalveolar lavage fluid; Bronchoscopy; Bronhoalveolarni izpirek, tekočina; Bronhoskopija; Cross infection; Diagnosis; diagnostika; Drug resistance, microbial; Drug therapy; Enote za intenzivno medicino; Escherichia coli; Intensive care units; Microbiology; Pljučnica; Pneumonia; Pseudomonas aeruginosa; Psevdomonas aeruginoza; Stafilokok aureus; Staphylococcus aureus; Streptococcus pneumoniae; therapy; Zdravila, rezistenca mikrobna; zdravljenje